To study factors that influence the accuracy of technical analysis when investing in stock market / Mohd Fazrel Hasan - Hasan, Mohd Fazrel (Faculty of Business and Management, 2011)
From author, (Dominic Hawker, 2004) said that rather than dwell upon the wonders of the Phoenician market for olive oil forwards, or the ancient Japanese and Chinese history of rice trading, this story starting with one Charles Dow, inventor of the first stock market index in 1884. After he noticed that by the time important corporate news entered the public domain, Charles Dow invented point and figure chart then the share price had moved, due not least to insider trading. Next, he has watched open market in US then him writing down prices in his laptop, looking for clues about market action. After that, Charles Dow still cannot find answer regarding to price movement. Therefore, he decides to plot price action in graphic form. Charles Dow also wrote a series of articles for the Wall Street Journal in the latter years of the 19th century. This body of work became known as ―Dow Theory and formed the initial basis for what we know as technical analysis today. The most important concepts that Mr. Dow recognized were that prices reflect the current balance of supply and demand example like the hopes and fears of investor and most importantly, an imbalance of supply and demand causes prices to form recognizable trends, up and down. In 1940s to 1950s, additional pioneers of technical analysis such as Bill Jiler, Robert Edwares, John Magee, Alexander Wheelan and Abe Cohen were making steady progress, not only in the types of charts used to show trends, but also techniques for analyzing price action.